Basic Concepts of Islamic Education According to the Ministry of Religion in Indonesia - Happy Ariesty Sumarsana; Fristy Nur Firdausy; Nur Aisyah (Universitas Muhammadiyah Surakarta, 2025)
The article explores the fundamental concepts of Islamic education as outlined by the Ministry of Religion in Indonesia. It addresses the significance of integrating religious values into educational practices to foster moral and ethical development among students. The research employs a qualitative approach, analyzing various documents and guidelines provided by the Ministry. The findings highlight key principles such as the integration of faith and knowledge, character building, and community involvement. In conclusion, the study emphasizes the need for a holistic educational framework that aligns with Islamic teachings.